Pengaruh Jenis Pelarut Terhadap Kadar Total Fenolik dan Flavonoid Daun Kayu Bulan - Anni Satul Qodariyah; Anggun Saputri; Rizqa Salsabila Firdausia; Kholif Sholehah Indra Kurniasih (JOURNAL OF PHARMACEUTICAL (JOP), 2024)
Kayu bulan leaves (Pisonia alba Span.) is one of the ornamental plants that contains secondary metabolites in the form of phenolic and flavonoids compounds, that contains secondary metabolites in the form of phenolic and flavonoids compounds. The extraction of phenolic and flavonoid compounds was carried out by ultrasonic wave-assisted method (UAE). Phenolic and flavonoid compounds have polar and non-polar properties that can be extracted using solvents such as 70% ethanol, methanol and ethyl acetate. This study aims to determine the effect of solvent type (70% ethanol, methanol and ethyl acetate) on total phenolic and flavonoids content in kayu bulan leaves extract extracted using the UAE method. This research was conducted by analyzing qualitatively using Thin Layer Chromatography method and quantitative using UV-Vis Spectrophotometry. test results, it shows that the kayu bulan leaves extract positively contains flavonoids and phenolics. Quantitative results showed that the total phenolic content was respectively; 70 % ethanol extract (16.2085 ± 0.7359) mg GAE/gram, extract methanol extract (24.3005 ± 0.7305) mg GAE/gram and ethyl acetate extract (28.5957 ± 0.7305) mg GAE/gram. Meanwhile, the total flavonoid content in 70% ethanol extract was 21.28 ± 0.473 mg QE/g, methanol extract was 58.68 ± 1.767 mg QE/g, and ethyl acetate extract was 118.152 ± 2.146 mg QE/g. It can be concluded that the highest total flavonoid and phenolic content was obtained in the ethyl acetate extract.